Exploration of Mechanisms behind Changes after Participation in a Parenting Intervention: A Qualitative Study in a Low‐Resource Setting. Issue 1 (30th March 2016) - Mejia, Anilena; Ulph, Fiona; Calam, Rachel
Abstract: Parenting interventions are effective for preventing psychological difficulties in children. However, their active ingredients have not been comprehensively explored. How do they work? What are the mechanisms operating behind changes? In 2012, a randomized controlled trial of a parenting intervention was conducted in low‐resource communities of Panama. Effects on child behavioral difficulties, parental stress, and parenting practices were large in the short and long term. This was an ideal opportunity to explore potential mechanisms operating behind effects found in this low‐resource setting. Twenty‐five parents were interviewed. Data were analyzed through an inductive semantic thematic analysis. Three themes emerged from the data: (a) psychological mechanisms behind changes, (b) behavioral changes in parent, and (c) changes in the children. Parents described that the intervention triggered changes in emotion regulation, self‐efficacy, and problem solving. Parents also reported behavioral changes such as praising their children more often, who in turn seemed more responsible and better at following instructions. The study offers participant‐driven insight into potential pathways of change after participation in this parenting intervention, pathways that are often overlooked in quantitative studies. Future studies should further explore these pathways, through mediator and moderator analyses, and determine how much is shared across interventions and across different cultural settings.